The gelechiid fauna of the southern Ural Mountains, part II: list of recorded species with taxonomic notes (Lepidoptera: Gelechiidae) - Junnilainen, Jari; Karsholt, Ole; Nupponen, Kari; Kaitila, Jari-Pekka; Nupponen, Timo; Olschwang, Vladimir (Zootaxa, 2010)
A list comprising 236 species in the family Gelechiidae from the southern Ural Mountains is presented. The material was collected during 1996–2007 on 21 different Finnish-Russian expeditions. The following new combinations are proposed: Caulastrocecis interstratella (Christoph, 1873) comb. n., Megacraspedus balneariellus (Chrétien, 1907) comb. n., Megacraspedus fallax (Mann, 1867) comb. n., Megacraspedus lagopellus Herrich-Schäffer, 1860 comb. rev., Megacraspedus niphorrhoa (Meyrick, 1926) comb. n., Scrobipalpa adaptata (Povolný, 2001) comb. n., Scrobipalpa dorsoflava (Povolný, 1996) comb. n., Scrobipalpa notata (Povolný, 2001) comb. n. and Scrobipalpa punctata (Povolný, 1996) comb. n. Neofriseria mongolinella Piskunov, 1987 stat. rev. is raised to the species rank (from subsp. of N. sceptrophora (Meyrick, 1926)). Previously unknown females of four species are described: Megacraspedus niphorrhoa (Meyrick, 1926), Monochroa nomadella (Zeller, 1868), Ivanauskiella psamathias (Meyrick, 1891) and Filatima zagulajevi Anikin & Piskunov, 1996. Trichembola neurophanes (Meyrick, 1926) syn. n. is shown to be a synonym of Megacraspedus fallax (Mann, 1867). Three separate species complexes are briefly discussed: Stomopteryx mongolica Povolný, 1975, Stomopteryx remissella (Zeller, 1847) and Aristotelia subericinella (Duponchel, 1843); each of them seems to contain unresolved taxonomic problems. Three species are reported for the first time from Europe: Neofriseria mongolinella Piskunov, 1987, Stomopteryx mongolica Povolný, 1975, and Anarsia sibirica Park & Ponomarenko, 1996. The following species are newly recorded from Russia: Apatetris kinkerella (Snellen, 1876), Catatinagma trivittellum Rebel, 1903, Megacraspedus balneariellus (Chrétien, 1907), Megacraspedus niphorrhoa (Meyrick, 1926), Chrysoesthia falkovitshi Lvovsky & Piskunov, 1989, Metzneria diffusella Englert, 1974, Ptocheuusa paupella (Zeller, 1847), Ptocheuusa abnormella (Herrich-Schäffer, 1854), Monochroa parvulata Gozmány, 1957, Eulamprotes plumbella (Heinemann, 1870), Aroga aristotelis (Millière, 1876), Filatima transsilvanella Z. Kovács & S. Kovács, 2001, Scrobipalpa adaptata (Povolný, 2001), Scrobipalpa dorsoflava (Povolný, 1996), Scrobipalpa halonella (HerrichSchäffer, 1854), Scrobipalpa lutea Povolný, 1977, Scrobipalpa magnificella Povolný, 1967, Scrobipalpa notata (Povolný, 2001), Scrobipalpa plesiopicta (Povolný, 1969), Scrobipalpa pulchra (Povolný, 1967), Scrobipalpa punctata (Povolný, 1996), Scrobipalpula diffluella (Frey, 1870), Caryocolum amaurella (M. Hering, 1924), Caryocolum repentis Huemer & Luquet, 1992, Syncopacma incognitana Gozmány, 1957, Syncopacma azosterella (Herrich-Schäffer, 1855), Syncopacma polychromella (Rebel, 1902), Brachmia procursella Rebel, 1903.